AN INTERPRETING ANALYSIS OF SHINee’s HIT - Rachmijati, Cynantia (IKIP Siliwangi, 2018)
With the development of music, one of music industry that recently has been well-known all over the world is K-Pop or Korean pop. Music from the South Korean also invaded many souls in their process and make it Korean musician and stars are now famous faces. One of the famous names from the K-Pop industry is SHINee, a boyband consists of 4 members. This paper entitled “An interpreting analysis of SHINee’s hit singles” is an interpreting analysis of 10 SHINee’s hit singles taken from the album “SHINee World” and “Lucifer” aimed to see what linguistic factors that make them hit. This research used a qualitative method. This research concluded that SHINee songs makes it hit because of numerous factors such as: the music, the instrument, the singing style and the lyric with figurative languages. In academic environments, teachers may teach the students how to analyze song lyric because it is useful. Not only to teach vocabulary, idiom but also elements of poetry.